Relación del rendimiento académico con hábitos de estudio y estilos de vida saludables en estudiantes universitarios. (2023)
Objective: to identify the academic performance of dental students in relation to study habits and lifestyles. description and methods, a cross-sectional descriptive observational study was carried out, 140 students from the Neiva and Palmira campuses of the Antonio Nariño University of Dentistry were evaluated, in which the variables of study habits and healthy lifestyles were evaluated against performance. academic.